2010
DOI: 10.1080/07438141003666848
|View full text |Cite
|
Sign up to set email alerts
|

Testing a methodology for assessing plant communities in temperate inland lakes

Abstract: (2010) Testing a methodology for assessing plant communities in temperate inland lakes, Lake and Reservoir Management, 26:1, 54-62,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 33 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…Our results indicated that in well preserved coastal systems, where habitat types can extend for several meters, the reduction in the number of plots did not affect the representation of habitats, maintaining comparable values of mean species richness, cumulative number of species as well as the number of the indicator species detected. Our findings are consistent with those of Mikulyuk et al (2010), who stated that a higher sampling effort does not always result in an increase in data accuracy and completeness. Indeed, different results emerged only in the comparison of habitats with a narrow extent, represented by a low number of plots (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicated that in well preserved coastal systems, where habitat types can extend for several meters, the reduction in the number of plots did not affect the representation of habitats, maintaining comparable values of mean species richness, cumulative number of species as well as the number of the indicator species detected. Our findings are consistent with those of Mikulyuk et al (2010), who stated that a higher sampling effort does not always result in an increase in data accuracy and completeness. Indeed, different results emerged only in the comparison of habitats with a narrow extent, represented by a low number of plots (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…A sample of a point-intercept map is shown in Figure 3. A more detailed description of this method is found in Mikulyuk et al (2010).…”
Section: Methodsmentioning
confidence: 99%
“…Lakes were sampled from a boat mid-June through August using the point-intercept survey methodology outlined by Hauxwell et al (2010). This methodology has been shown to return robust and predictable species frequency data and is suitable for making comparisons among lakes (Mikulyuk et al 2010). Following this protocol, survey grids were constructed based on littoral area and shoreline complexity.…”
Section: Aquatic Macrophyte Datamentioning
confidence: 99%